2012
DOI: 10.1002/jms.2974
|View full text |Cite
|
Sign up to set email alerts
|

Revealing the glycation sites in synthetic neoglycoconjugates formed by conjugation of the antigenic monosaccharide hapten of Vibrio cholerae O1, serotype Ogawa with the BSA protein carrier using LC‐ESI‐QqTOF‐MS/MS

Abstract: In this manuscript, we present the determination of glycation sites in synthetic neoglycoconjugates formed by conjugation of the antigenic monosaccharide hapten of Vibrio cholerae O1 serotype Ogawa to BSA using nano- liquid chromatography electrospray ionization quadrupole time-of-flight tandem mass spectroscopy (LC-ESI-QqTOF-MS/MS). The matrix-assisted laser desorption/ionization-TOF/TOF-MS/MS analyses of the tryptic digests of the glycoconjugates having a hapten:BSA ratio of 4.3:1, 6.6:1 and 13.2:1 revealed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 21 publications
(48 reference statements)
0
6
0
Order By: Relevance
“…[2023] Based on this, the m/z value of the peptides that did not match to any protein were compared with a table model containing hypothetical molecular weight values of all possible hapten hexasaccharide conjugated to lysine residues of tryptic peptide of the tetanus toxin protein. Subsequently, the mass spectra of each possible glycated peptide were manually processed, looking for the carbohydrate-linker signature product ions, as well as the corresponding peptide sequence.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[2023] Based on this, the m/z value of the peptides that did not match to any protein were compared with a table model containing hypothetical molecular weight values of all possible hapten hexasaccharide conjugated to lysine residues of tryptic peptide of the tetanus toxin protein. Subsequently, the mass spectra of each possible glycated peptide were manually processed, looking for the carbohydrate-linker signature product ions, as well as the corresponding peptide sequence.…”
Section: Resultsmentioning
confidence: 99%
“…As observed in our previous studies, all the identified glycation sites are located exclusively on lysine residues. [2023] This suggests that while the squaric acid chemistry allows an amino acid specific conjugation, it does not allow a site specific conjugation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the determination of the average number of carbohydrate‐spacer moieties linked to BSA (TF antigen:BSA), the two glycoconjugates were analyzed by matrix assisted laser desorption/ionization‐mass spectrometry (Fig. a and b and Table ) . The MALDI‐TOF‐MS was characterized by the formation of a protonated molecular ions [M + H] + at m/z 67 599 and 70 905 and their TF–BSA ratios were calculated to be individually 2:1 and 8:1.…”
Section: Resultsmentioning
confidence: 99%
“…BSA is one of the most widely studied proteins used as a carrier protein for the synthesis of neoglycoconjugates. [27,[37][38][39][40][41] BSA contains 35 cysteine residues linked by S-S disulphide bonds among which, however, there is only a single buried free cysteine residue (Cys34) [42] that has been systematically used for other conjugation. [43,44] It is known that the 35 cysteine residues of BSA form 17 disulphide bonds at these positions (1) (17) 581-590 .…”
Section: Synthesis Of the Tf-bsa Vaccine Conjugate By The Michael Addmentioning
confidence: 99%